2016
DOI: 10.5935/0103-507x.20160010
|View full text |Cite
|
Sign up to set email alerts
|

Lung hyperinflation by mechanical ventilation versus isolated tracheal aspiration in the bronchial hygiene of patients undergoing mechanical ventilation

Abstract: ObjectiveTo determine the efficacy of lung hyperinflation maneuvers via a mechanical ventilator compared to isolated tracheal aspiration for removing secretions, normalizing hemodynamics and improving lung mechanics in patients on mechanical ventilation.MethodsThis was a randomized crossover clinical trial including patients admitted to the intensive care unit and on mechanical ventilation for more than 48 hours. Patients were randomized to receive either isolated tracheal aspiration (Control Group) or lung hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
1
12
0
9
Order By: Relevance
“…Since then, many studies on ventilator hyperinflation have been carried out with general samples of critical care patients. [30][31][32][33][34] These studies confirmed the similarity between ventilator hyperinflation and manual hyperinflation in clearing secretions, improving respiratory mechanics, and gas exchange. 30,32,33 Nevertheless, there is a lack of studies addressing the effects of ventilator hyperinflation or manual hyperinflation on long-term clinically relevant outcomes, such as length of stay, duration of mechanical ventilation, weaning, and incidence of ventilator-associated pneumonia.…”
Section: Ventilator Hyperinflationsupporting
confidence: 54%
See 2 more Smart Citations
“…Since then, many studies on ventilator hyperinflation have been carried out with general samples of critical care patients. [30][31][32][33][34] These studies confirmed the similarity between ventilator hyperinflation and manual hyperinflation in clearing secretions, improving respiratory mechanics, and gas exchange. 30,32,33 Nevertheless, there is a lack of studies addressing the effects of ventilator hyperinflation or manual hyperinflation on long-term clinically relevant outcomes, such as length of stay, duration of mechanical ventilation, weaning, and incidence of ventilator-associated pneumonia.…”
Section: Ventilator Hyperinflationsupporting
confidence: 54%
“…Moreover, different from manual hyperinflation, ventilator hyperinflation makes it possible to monitor and set the parameters of interest for the technique's application. 32,33,35 Studies on ventilator hyperinflation have used different criteria to determine the inspiratory volume: 50% above the current tidal volume, 34 130% of the set tidal volume, 32 15 mL/kg, 33 and volume corresponding to a peak inspiratory pressure of 40 cm H 2 O. 30,31,35 Regardless of the criteria chosen, the peak inspiratory pressure was limited to 40 cm H 2 O.…”
Section: Ventilator Hyperinflationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that lung hyperinflation techniques can improve pulmonary oxygenation and compliance and reverse lung collapse and atelectasis. ( 2,7-10,15 ) This is due to the ability of hyperinflation to increase TV, leading to the expansion of both ventilated and collapsed alveoli; this phenomenon is explained by the pulmonary interdependence mechanism, which facilitates the transport of secretions from the peripheral airways to the central airways. ( 15,16 )…”
Section: Discussionmentioning
confidence: 99%
“…Além da influência da pressão positiva aplicada às vias aéreas, a ventilação dos alvéolos será dependente da ação da gravidade, fazendo com que regiões do pulmão não dependentes (i.e., sem contato com a cama) gerem pressões pleurais mais negativas, convergindo para expansão passiva. Nesse contexto, regiões pulmonares colapsadas devem ser posicionadas de forma não dependente da gravidade, pois serão passivamente expandidas 33,34 . A postura assumida pelos pacientes é fundamental nesse contexto.…”
Section: Posicionamento Terapêuticounclassified